P142 Inflammatory cells in the quadriceps of COPD patients and response to resistance training. (16th November 2010) - Menon, M K; Houchen, L; Harrison, S; Singh, S J; Morgan, M D L; Bradding, P; Steiner, M C
Abstract : Background: Physical exercise in healthy individuals leads to an acute inflammatory-cell response in skeletal muscles. In COPD, quadriceps dysfunction is an important systemic manifestation that can be offset by exercise training. However, the nature of the muscle inflammatory response in these patients to acute and chronic exercise remains unknown. We therefore measured inflammatory cell infiltration in the quadriceps of COPD patients and healthy controls, in response to a programme of lower-limb resistance training. Methods: 12 COPD patients (mean (SD) age 66.7(7.0) years, BMI 26.1(7.2) kg/m 2, FEV1 46.4 (20.5) % predicted, 10 males) and seven healthy controls (66.7 (5.1) years, BMI 27.7(2.4) kg/m 2, FEV1 103.4 (17.0) % predicted, five males) underwent 8 weeks of bilateral lower-limb, high-intensity resistance training, thrice weekly, on an isokinetic dynamometer (Cybex II Norm). Quadriceps muscle biopsies from the dominant thigh were obtained at baseline (T0), 24-h after the 1st exercise bout (T1), and 24-h after the last exercise session following 8-weeks training (T2). Glycol methacrylate-embedded muscle biopsies were analysed using immunohistochemistry. Inflammatory cells were identified using antibodies against neutrophil elastase (NE) and CD163 (macrophages). Dual energy x-ray Absorptiometry (DEXA) was used to determine thigh muscle mass and isometric quadriceps strength was measured on the cybex. Results: At T0, neutrophils were not detected in any of the healthy controls, but were present in six out of 12 patients. A significant increase in neutrophil and macrophage counts in both patients and controls was seen at T1 (Abstract P142 Table 1 ). At T2, inflammatory cell counts in both groups were close to baseline values. Isometric quadriceps strength (COPD: pre vs post -134.0 (44.0) vs 151.8 (47.9) Nm, p=0.002; Healthy: pre vs post 153.4 (42.4) vs 169.0 (43.1) Nm, p=0.04] and thigh lean mass (COPD: pre vs post 4.4 (1.2) vs 4.7 (1.2) kg, p=0.003; Healthy: pre vs post 4.5 (0.6) vs 4.7 (0.7) kg, p=0.004] increased significantly after training in both groups. Conclusions: Acute resistance exercise in COPD leads to an inflammatory-cell response in the quadriceps that is comparable to healthy controls. Regular training results in muscle adaptation characterised by a diminished inflammatory response to a bout of exercise.